The Islamic Education Viewpoint on Preventing Premarital Sex Dangers Through Reproductive Education - Suprima, Suprima (Jurnal Penelitian Pendidikan Islam, 2022)
Providing sex education for a teenager is substantial in the perspective of Islam. However, teaching sex education from an Islamic perspective should not be arbitrary. Teenagers and kids are vulnerable to getting false information about sexual activity knowledge. This study aims to indicate that sex education in the Islamic perspective would be a move to prevent risky sexual behaviour. In this study, we use the qualitative research method with literature review or literature study by reviewing numbers of relevant literature to be analyzed and concluded. Deduced from al-Qur'an and hadith, providing education about sexual activity for teenagers in the perspective of Islam along with educating them in accordance to exemplified by the Prophet Muhammad would prevent teenagers from having risky premarital sex.